2020
DOI: 10.3390/ijerph17010336
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Interdisciplinary Program Performed on Obese People Regarding Nutritional Habits and Metabolic Comorbidity: A Randomized Controlled Clinical Trial

Abstract: Obesity is an important public health problem. The combined use of different therapies performed by an interdisciplinary group can improve the management of this health issue. The main goal of this research is to determine the effectiveness of a multidisciplinary program based on healthy eating, exercise, cognitive-behavioral therapy, and health education in improving metabolic comorbidity, Body Mass Index (BMI), and nutritional habits among obese adults, at short (12 months) and long term (24 months). A rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Included trials (see supplementary table 1) were individual randomised controlled trials (n=25) 24 25 26 27 28 29 32 33 34 35 38 39 41 44 45 46 47 50 51 52 53 54 55 56 59 or cluster randomised controlled trials (n=9). 23 30 31 36 37 48 49 57 58 Most were conducted in the US (n=14), 29 30 31 32 33 34 35 36 37 45 48 51 54 55 UK (n=7), 27 28 38 41 47 57 58 and Spain (n=4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Included trials (see supplementary table 1) were individual randomised controlled trials (n=25) 24 25 26 27 28 29 32 33 34 35 38 39 41 44 45 46 47 50 51 52 53 54 55 56 59 or cluster randomised controlled trials (n=9). 23 30 31 36 37 48 49 57 58 Most were conducted in the US (n=14), 29 30 31 32 33 34 35 36 37 45 48 51 54 55 UK (n=7), 27 28 38 41 47 57 58 and Spain (n=4).…”
Section: Resultsmentioning
confidence: 99%
“… 23 30 31 36 37 48 49 57 58 Most were conducted in the US (n=14), 29 30 31 32 33 34 35 36 37 45 48 51 54 55 UK (n=7), 27 28 38 41 47 57 58 and Spain (n=4). 25 44 46 49 The median number of participants was 276 (range 50-864).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was based on the I 2 AO 2 program, which has demonstrated particularly good efficacy in overweight and obese adults from the same geographical setting (Fernández-Ruiz, Armero-Barranco, et al, 2018), resulting in reduced cardiometabolic comorbidity (Fernández-Ruiz et al, 2018a) and improved eating habits and sedentary behavior, together with a positive impact upon quality of life (Fernández-Ruiz et al, 2018b, 2020). In this work, the participants were randomly assigned to two groups and the trial was conducted over one school year (i.e., 9 months from 1 September 2015 to 30 June 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Some recent, nurse-led multidisciplinary programs such as the Interdisciplinary Intervention Against Overweight and Obesity (I 2 AO 2 ) intervention have demonstrated the efficacy of addressing obesity and metabolic comorbidity in obese adults, resulting in weight loss and the modification of both eating and physical activity habits (Fernández-Ruiz et al, 2018b, 2020). This program is based on healthy eating education, physical exercise, and cognitive behavioral therapy (CBT), and poses no additional costs.…”
mentioning
confidence: 99%